PERSIAPAN PERSALINAN DI MASA PANDEMI PADA IBU TRIMESTER 3 - Ibrahim; Arum Dwi Anjani; Yollanda Dwi Santi; Yani Aprilia Purba (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
The maternal mortality rate in 2019/2020 was 306 per 1000 birth rates. The purpose of this study was to provide information and increase knowledge of pregnant women about health and information about the importance of conducting prenatal care during the COVID 19 pandemic. The level of delivery readiness is still very low, especially during the pandemic this affects the limitation of ANC services for pregnant women, ANC visits have decreased since the pandemic period, even though there is evidence that mothers who rarely do ANC will be at risk of experiencing interference during pregnancy and can even be at risk At the time of the preparation stage, there will be socialization to pregnant women related to pregnancy, and at the implementation stage, material about pregnancy will be given and finally at the evaluation stage, it will be carried out. There was a question session related to pregnancy, this activity was carried out in Batu Aji, Sagulung sub-district, and the target of this activity was 30 pregnant women. This counseling proved useful to increase the knowledge of pregnant women about the importance of health and the importance of carrying out pregnancy checks.